Human West Nile Virus Disease Outbreak in Pakistan, 2015–2016 - Khan, Erum; Barr, Kelli L.; Farooqi, Joveria Qais; Prakoso, Dhani; Abbas, Alizeh; Khan, Zain Yar; Ashi, Shanze; Imtiaz, Kehkashan; Aziz, Z.; Malik, Faisal; Lednicky, John A.; Long, Maureen T. (Frontiers in Public Health, 2018)
: Like most of the world, Pakistan has seen an increase in mosquito-transmitted diseases in recent years. The magnitude and distribution of these diseases are poorly understood as Pakistan does not have a nation-wide system for reporting disease. A cross-sectional study to determine which flaviviruses were the cause of arboviral disease in Pakistan was instituted. West Nile Virus (WNV) is a cause of seasonal fever with neurotropic findings in countries that share borders with Pakistan. Here we describe the active and persistent circulation of WNV in humans in the southern region of Pakistan. This is the first report of WNV causing neurological disease in human patients in this country. Out of 997 enrolled patients presenting with clinical features suggestive of arboviral disease, 105 were positive for WNV IgM antibodies and 71 of these patients possessed WNV-specific neutralizing antibodies. Cross-reactivity of WNV IgM antibodies with Japanese Encephalitis Virus (JEV) occurred with 75 of these 105 patients. WNV co-infections with Dengue viruses were not a contributing factor for the severity of disease. Nor did prior exposure to dengue virus contribute to incidence of neurological involvement in WNV infected patients. Patients with WNV infections were more likely to present with altered mental status, seizures, and reduced Glasgow Coma scores when compared with JEV infected patients. Human WNV cases and vector numbers exhibited a temporal correlation with climate.